Advantages and disadvantages of blended learning in the academic performance of 8th semester PINE major students - Robalino Mendoza, Ivette Micaela (2023)
Blended Learning is the combination of two learning modalities: face-to-face and virtual. During the university major, stages that emerged through the pandemic and post-pandemic were experienced, which implied the adaptation of B-Learning for the continuity of the education of the students and their performance. For this reason, the objective of this research project was to analyze the influence of B-Learning on students who are currently in the last course of PINE, specifically in eighth semester, identifying the advantages and disadvantages. In this project, the qualitative methodology was used, and the data obtained was through a one-on-one interview with open questions. The main findings showed that the disadvantages outweigh the advantages, since the virtual modality accustomed the students to the ease, therefore, the return to the face-to-face modality became a challenge since it was necessary to put aside the dependence on the Internet, affecting the level of English in a negative aspect.